[Two students in a Red Brick dorm] (1977)
One student reclining on a bed and another sitting backwards in a chair. The dorm room contains a turntable and a wall covered in posters and calendars, images, and an Alpha Epsilon Pi star badge, pamphlets and flyers, as well as a hat under glass and records on the shelves.